2020
DOI: 10.1007/s13659-020-00254-0
|View full text |Cite
|
Sign up to set email alerts
|

Artemlavanins A and B from Artemisia lavandulaefolia and Their Cytotoxicity Against Hepatic Stellate Cell Line LX2

Abstract: Two new sesquiterpenoids, artemlavanins A ( 1 ) and B ( 3 ), together with fifteen known compounds ( 2 and 4−17 ) were isolated from the EtOH extract of Artemisia lavandulaefolia . The structures of new compounds were elucidated by extensive spectroscopic analyses (HRESIMS, 1D and 2D NMR) and ECD calculations. Compound 1 was a sesquiterpenoid lactone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The cytotoxicity assay of compounds was conducted by referring to our previous papers. [30][31][32] Please see the ESI. †…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity assay of compounds was conducted by referring to our previous papers. [30][31][32] Please see the ESI. †…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…The Col I, HA and HL secretion assay of compound 1 was performed with reference to our previous papers. [30][31][32] Please see the ESI. †…”
Section: Col I Ha and Hl Secretion Assaymentioning
confidence: 99%
“…In particular, artematrolides A, J, and K and lavandiolide H showed cytotoxicity equal to or superior to that of sorafenib with IC 50 values ranging from 3.8 to 9.6 μM. Importantly, lavandiolide H could inhibit cell migration and invasion and induce G2/M cell cycle arrest and cell apoptosis in HepG2 cells. , Artematrolide A also exhibited significant inhibitory activity on HeLa S3 and SiHa cell lines via the ROS/ERK/mTOR pathway and a metabolic shift . Simultaneously, Ye et al reported the isolation of lavandiolides A–L from Artemisia lavandulifolia and suggested that lavandiolides A, C, G, and I showed potent inhibitory effects on NO production in LPS-stimulated macrophages with IC 50 values of 0.61, 1.64, 1.89, and 1.40 μM, respectively .…”
mentioning
confidence: 93%
“…In our search for antiheptoma sesquiterpenoids from Artemisia species, , 25 guaianolide dimers, artematrolides A–R, lavandiolides A–C, H, and J, and artematrodimers A and B were isolated from Artemisia atrovirens . Biological assessment indicated these compounds possessed obvious cytotoxicity against HepG2, SMMC-7721, and Huh7 cell lines.…”
mentioning
confidence: 99%
“…The synthesis of lavandiolides H, I, and K and artematrolide F via a biomimetic Diels−Alder reaction was accomplished in our laboratory [ 19 ]. Ludartin, a 6,12-guaianolide isolated from A. lavandulaefolia [ 20 ], exhibited moderate cytotoxicity against HepG2 and Huh7 cell lines with IC 50 values of 32.7 and 34.3 μM, respectively. Ludartin was first isolated from A. carruthii [ 21 ], which was also found in Stevia yaconensi [ 22 ] and other Artemisia species [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%